Silowo Ecotourism: Development Strategy to Enhancing Community Welfare in Mandirejo Village, Merakurak District, Tuban - Sholeh, Mochamad; Salasa, M. Ibnu; Mustofa, Riza; Nababan, Lambok (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
Mandirejo Village, located in Tuban Regency, is one of the areas that has natural resources that have great potential in the tourism sector, one of which is located in Silowo Village. The purpose of this study was to describe how the development strategy of Silowo Village became a tourist attraction in Mandirejo Village, the sustainability strategy of tourism development, and efforts to improve welfare for the community around the Silowo tourist attraction in Mandirejo Village. This research uses a qualitative approach with a descriptive type. Data collection in this study was carried out using observation, interview, and documentation techniques. The results of this study found that the development strategy of the Silowo Ecotourism is done in stages, and the implementation of sustainability strategies in Silowo village has switched to digital marketing, namely by intensifying promotion through social media and uploading the latest developments in Silowo tourism and the impact obtained from tourism development, including the creation of jobs, an increase in income, and building community independence.